Programa de promoción de la salud en la adopción de los estilos de vida saludables en el personal de servicios general y mantenimiento de la Universidad Antonio Nariño sede Bogotá (2021)
This project seeks to inform and respond to the healthy lifestyles of general services and maintenance personnel during the pandemic period at the Antonio Nariño University, Bogotá headquarters. This purpose conforms to the assumption of the International Labor Organization together with the World Health Organization, which seek the well-being of all workers. Therefore, one of its main objectives is to reduce the rate of occupational accidents and occupational diseases.